The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/aos.13444
|View full text |Cite
|
Sign up to set email alerts
|

Glistenings, anterior/posterior capsular opacification and incidence of Nd:YAGlaser treatments with two aspheric hydrophobic acrylic intraocular lenses – a long‐term intra‐individual study

Abstract: Visual outcomes, PCO development over time and need for Nd:YAG laser treatment were similar for the two IOLs. Anterior capsule fibrosis/contraction and glistenings were more pronounced with the SN60WF IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…However, although a clear improvement can be seen for the SN60WF, the MA60AC IOLs showed that glistenings may still exist in other AcrySof lenses, also those manufactured after 2012 (De Soyza J, et al RANZCO 2017, Abstract number: S1902). 15,45 This problem may be resolved by the new Clareon material introduced by Alcon, which was shown to be glistenings-free in preclinical in vitro studies (Auffarth GU, ESCRS 2017).…”
Section: Straylight Measurementsmentioning
confidence: 99%
“…However, although a clear improvement can be seen for the SN60WF, the MA60AC IOLs showed that glistenings may still exist in other AcrySof lenses, also those manufactured after 2012 (De Soyza J, et al RANZCO 2017, Abstract number: S1902). 15,45 This problem may be resolved by the new Clareon material introduced by Alcon, which was shown to be glistenings-free in preclinical in vitro studies (Auffarth GU, ESCRS 2017).…”
Section: Straylight Measurementsmentioning
confidence: 99%
“…Ton Van et al and Johansson et al reported the 3-year cumulative incidence of PCO requiring Nd:YAG laser capsulotomy, ie, 2.2% and 10.0%, respectively. 4 , 5 However, Baratz et al reported 6% at 1 year, which increased to 38% at 9 years. 6 …”
Section: Discussionmentioning
confidence: 98%
“…Teshigawara et al capsulotomy, ie, 2.2% and 10.0%, respectively. 4,5 However, Baratz et al reported 6% at 1 year, which increased to 38% at 9 years. 6 Nd:YAG laser treatment is a generally safe method to relieve the symptoms of PCO, such as reduction in visual acuity, haze, and glare.…”
Section: Dovepressmentioning
confidence: 99%
“…The most frequent postoperative complication of a successfully performed cataract surgery is the development of posterior capsule opacification (PCO), also known as the secondary cataract [4] (Figure1). It could provoke the decrease of the best-corrected visual acuity, reduction of contrast sensitivity, glare occurrence, or monocular diplopia [4]. PCO is caused by proliferation and migration of the remaining residual epithelial cells.…”
Section: The Effect Of Intraocular Lens Materials and Postoperative Thmentioning
confidence: 99%